2019
DOI: 10.1021/acs.jafc.9b04415
|View full text |Cite
|
Sign up to set email alerts
|

Co-encapsulation of Epigallocatechin Gallate (EGCG) and Curcumin by Two Proteins-Based Nanoparticles: Role of EGCG

Abstract: In this study, a novel plant-protein-based nanoparticle delivery system was developed to encapsulate and stabilize curcumin and epigallocatechin gallate (EGCG) with different polarities. The strongly hydrophobic curcumin was embedded within the hydrophobic cores of zein nanoparticles using an antisolvent method, while the weakly hydrophobic EGCG was adsorbed to the region between the zein core and caseinate shell. The physicochemical properties, structure, and stability of the core−shell particles were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 42 publications
0
56
0
Order By: Relevance
“…The functional properties of colloidal delivery systems are associated with the particle size, PDI, and charge characteristics [ 27 ]. It has been reported that nanoparticles with particle sizes in the range of 10–100 nm have unique advantages such as enhanced solubility and stability [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional properties of colloidal delivery systems are associated with the particle size, PDI, and charge characteristics [ 27 ]. It has been reported that nanoparticles with particle sizes in the range of 10–100 nm have unique advantages such as enhanced solubility and stability [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Simulate gastrointestinal digestion was operated according to the method of Yan et al [ 27 ], with some modifications. The sample was mixed with hydrochloric acid (0.1 M) and stirred (100 rpm/min) at 37 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Animal proteins, such as caseinate (Li, Xu, Sun, et al., 2018; Liu, Li, Yang, Xiong, & Sun, 2017; Yan et al., 2019; Zheng & Zhang, 2019), gelatin (Khan, Fang, et al., 2019; Mamidi, Romo, Leija Gutiérrez, Barrera, & Elías‐Zúñiga, 2018; Wang et al., 2018), beta‐lactoglobulin (β‐Lg) (Khan, Fang, et al., 2019), and whey protein isolate (WPI) (Oymaci & Altinkaya, 2016; Zhu et al., 2018) are often used to stabilize prolamin‐based particles. These proteins reduce the strong surface hydrophobicity of prolamins and increase the steric and electrostatic repulsions, thereby reducing their tendency to aggregate (Yan et al., 2019). WPI has also been used to couple gliadin to form emulsion gels using the ASP method (Zhu et al., 2018).…”
Section: Prolamin/protein Binary Complexesmentioning
confidence: 99%
“…This improvement was not only attributed to the nanocarrier, but also to the strong antioxidant activity of EGCG, which generates a synergic effect in combination with curcumin. 61 The encapsulation within zein-chitosan nanoparticles enhanced the water solubility of quercetin about 753 times, in comparison with free quercetin. Likewise, the antioxidant activity of the same compound on human liver cancer (HepG2) cells was also intensified by encapsulation using zein-chitosan as wall materials of nanoparticles, showing a decrease in the median effective dose (EC 50 ) by 24%.…”
Section: Polysaccharides For Phenolic Compounds Encapsulationmentioning
confidence: 99%